External Reference As A Pragmatic Mechanism For Meaning Construction A Pragmatic Textual Study/ الإحالة الخارجية كآلية تداولية لبناء المعنى دراسة نصية تداولية - Sidibe Ousmane; Mohammed Bin Dhafer Al-Hazmi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study investigates the relationship between pragmatics and external reference, considering external reference as one of the principal mechanisms of pragmatic analysis. It outlines the concepts of pragmatics and external reference, emphasizing their points of intersection on the grounds that external reference operates as a pragmatic device. The discussion then turns to the notions of intention and acceptance and their essential role in meaning construction, stressing that effective communication must rest on these two principles. The study further examines the speaker’s role and purposes in employing external reference, noting that one key aim is to stimulate the addressee’s cognitive engagement and involve them in co-constructing the text and generating meaning. On this basis, speakers are classified into two types: those who are aware of extralinguistic reality and those who are not. Attention is also given to the hearer’s role in accepting external reference, as an active participant in interpretation and meaning-making. The study concludes that external reference is directly tied to pragmatics, forming an integral component of it, and constitutes a vital tool in language teaching and learning, since it situates language within its actual performative context and links linguistic output to its extralinguistic environment.